Influence of Stress, Fatigue, Sleep and Delayed Onset Muscle Soreness on Perceived Physical Enjoyment Exertion during Small Sided Games - Okba SELMI; Nejmeddine OUERGHI; Wissam Ben KHALIFA; Nidhal JEBABLI; Moncef FEKI; Anissa BOUASSIDA (Tehran University of Medical Sciences, 2018)
No Abstract###